2011
DOI: 10.1177/147470491100900406
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Eliminates Female Advantage in Detection of Ambiguous Negative Affect

Abstract: The human stress response evolved to maximize an individual's probability of survival when threatened. The present study addressed whether physical danger modulates perception of an unrelated ambiguous threat and, if so, to what extent this response is sexspecific. The authors utilized a first-time tandem skydive as a stressor, which had been previously validated as producing a highly-controlled, genuinely stressful environment. In a counter-balanced within-subjects design, participants wore a virtual reality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Experiment 3 provides support for this hypothesis, but only "when the stakes are low" and the looming source has stopped a good distance away. The interaction of sex, vocalization, type, and distance is consistent with findings that show the female advantage in processing emotion can be significantly diminished under conditions of stress (DeDora et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Experiment 3 provides support for this hypothesis, but only "when the stakes are low" and the looming source has stopped a good distance away. The interaction of sex, vocalization, type, and distance is consistent with findings that show the female advantage in processing emotion can be significantly diminished under conditions of stress (DeDora et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…However, the current findings, along with those of DeDora et al (2011), may provide an explanation for failures to find differential effects of sex in processing infant laughs versus cries in neuroimaging studies (e.g., Seifritz, et al, 2003). The noise and confining nature of neuroimaging scanners can make them particularly stressful environments.…”
Section: Discussionmentioning
confidence: 54%
“…On the fifteen-minute plane ride leading up to the jump, subjects completed our Ambiguous Threat Detection Task, which we have previously shown to be responsive to stress (DeDora et al, 2011). The Ambiguous Threat Detection Task was designed to quantify the amount of signal/noise required for decision-making, dissociating perceptual and cognitive components.…”
Section: Behavioral Testing Of Threat Perceptionmentioning
confidence: 99%
“…Similarly, data reported by Herridge and colleagues [23] suggests that men who scored low on the Cook Medley Hostility scale and who were stressed through a cold pressor stressor perform slightly worse in recognizing emotional facial expressions than non-stressed participants. Stress does not only seem to influence facial emotion recognition accuracy , but it has also been reported that stressed participants respond more quickly when identifying emotions [24]. …”
Section: Introductionmentioning
confidence: 99%